SOCIAL CAPITAL OF FRESH FISH TRADERS IN THE MARKET OF PERAWANG, TUALANG SUB- DISTRICT, SIAK REGENCY - Tindaon, Rohmana Santi; Zulkarnain, Zulkarnain; Nugroho, Firman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTThis research was conducted in February 2020 at Perawang Market, Tualang Sub-District, Siak Regency.The purpose of this study is to determine the social forms that exist between fresh fish traders, suppliers and buyers in the Perawang Market and to find out how social capital continues to occur among fresh fish traders in the Perawang Market. The method used in this study is the census method with a qualitative descriptive approach. The population in this study was 16 informants.From the results of the study, obtained a form of social networking formed between fish traders who work together and help each other by giving each other information about fish. Norms in buying and determining prices are formed personally. Trust given by traders to buyers because of the closeness, honesty and getting to know each other between traders and buyers. To maintain the social capital of fresh fish traders, fresh fish traders continue to maintain a sense of unity and kinship between fellow traders, buyers, and suppliers / agents of fish.Keywords: Social capital, Traders, Markets, Networks, Norms, Trust